Development and validation of a questionnaire assessing challenges and competencies of crisis leadership in the public healthcare system - Nachia Banu Abdul Rahim; Fredie Robinson; Aizuddin Hidrus; Rudi Nasib; Abraham Chiu En Loong; Primus John; Prabakaran Solomon Dhanaraj (ResearchGate, 2024)
INTRODUCTION: During the pandemic, crisis leadership is being tested in ways the world hasn’t seen in generations, and leading through it has become a severe challenge for leadership in public health organisation. Therefore, this study aims to develop and validate a self-administered questionnaire (Crisis Leadership Questionnaire, CLQ) to assess the challenges and competencies faced and needed in crisis leadership. METHODS: The questionnaire describes the general sociodemographic data of the participant, assesses challenges in the organisation in the categories of structural (4 domain), political (3 domain), and cultural (3 domain), and also on the nine (9) competencies needed in crisis leadership. Ten (10) sociodemographic data-related questions with 90 questions (53 on the challenges and 37 on competencies) were reviewed by two experts for face validity, and exploratory factor analysis was performed, using principal axis factoring with Promax rotation, to establish the construct validity of the questionnaire. The internal consistency of the questionnaire was tested using Cronbach’s α coefficient. RESULTS: The final CLQ contained ten (10) sociodemographic questions, thirty-three (33) items focus on challenges categorized into structural (3 domains), political (2 domains), and cultural (3 domains) aspects, and twenty-two (22) items assess five key competencies required for crisis leadership. The content validity index (CVI) value is 0.96 for the challenges construct and 1.0 for the competencies construct, respectively, while the internal consistency reliability analysis (Cronbach’s alpha=> 0.6) is for all the domains. CONCLUSION: The developed questionnaire will help better understand the challenges and competencies of crisis leadership for current and future preparedness.